Ashley the dragon fairy - Meadows, Daisy (Meadows, Daisy. Magical animal fairies, 2012)
Rachel and Kirsty are going to an outdoor adventure camp, but Jack Frost has stolen the seven magical animals from their fairies and they must rush to help Ashley the Dragon Fairy get her dragon back.